THE PUPILLOMETRIC PREDICTOR OF INTERNET-ADDICTION - R V Ershova; T M Semina; N N Varchenko; K A Gankin; V P Novik (Peoples' Friendship University of Russia (RUDN University), 2016)
This study aims to investigate the possibilities of using binocular synchronous pupillography as a method of Internet addiction (IA) prediction.326 undergraduate students (179 females and 147 males, average age = 18,6) took part in this study. They were divided into three groups: "Internet addicted" (34 people), "not-addicted" (136 people), and "moderate-addicted", according to normal distribution of Chen's Addiction Scale results. The pupillography method was used to compare the IA symptoms in IA and Not-IA students.The total IA in pupillometric parameters was manifested as an increased width of the pupil, emotional instability, exhaustion, slack reactions, combined with the depth of reaction and impetuosity. The severity of Internet addiction was positively correlated with the number of pupillometric parameters.Our findings suggested that changes in pupil reaction were present in IA students and this finding may provide a new insight into the pathogenesis of IA.